BAKTI SOSIAL SUNATAN MASSAL DI PERUMAHAN GRIYA BATU AJI TAHAP 1 ,2 DAN 3 RW 16 KELURAHAN SUNGAI LANGKAI KECAMATAN SAGULUNG KOTA BATAM - Winda Evyanto; Mhd. Johan (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2022)
The cost of circumcision which is starting to become unaffordable to the public and coupled with the outbreak of the most frightening virus, namely "covid 19" and also the desire to create a clean and healthy young generation, the devotees intend to hold activities with the intention of sharing with others, namely holding social service activities "Mass Circumcision". This circumcision from a religious point of view is mandatory and also from a medical point of view, it has many benefits including maintaining physical cleanliness and reducing the risk of infection and the educational values ​​contained in it. The method used is the method of mass circumcision in the residential neighborhood of Griya Batu Aji Asri Phases 1,2 and 3, Sungai Langkai Exit, Sagulung sub-district, Batam City. It turns out that circumcision has educational value, for example, basically circumcision teaches children to become adults. From a psychological point of view, the child feels that he is a Muslim and he is obliged to cover his aurat and cannot see the nakedness of others. the educational values ​​contained in circumcision for children's education lies in the important role of parents to do the following: (1) Instill shame in children. (2) Instilling the spirit of masculinity in boys and the spirit of femininity in girls. (3) Separate their beds. (4) Introduce visiting times (ask permission within 3 times). (5) Educate to maintain the cleanliness of the genitals. (6) Introducing the muhrim. (7) Educate children to always keep their eyesight. One of the efforts with the aim that every teenager can perform circumcision is to organize a mass social service circumcision. Moreover, from the practice of mass circumcision it is believed that many young people in Indonesia can be circumcised, so this is achieved to further develop the welfare status and great development of Indonesian children.